TRANSFORMASI SUPERVISI PENDIDIKAN DI ERA TEKNOLOGI DIGITAL PADA KURIKULUM MERDEKA - Ayuningrum; Cucu Atikah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Supervision activities are related to controlling and measuring the effectiveness of learning using reliable scientific instruments. One of the supervision models developed on the basis of all-digital needs is the digital supervision model, although all supervision models need to be applied in independent learning. This study aims to analyze the transformation of educational supervision in the era of digital technology in the independent curriculum. The research method uses literature study with synthesis analysis and conclusions. Based on the analysis and discussion in this study, it can be concluded that the transformation of educational supervision in the Independent Learning curriculum can provide a change in professionalism and sophistication of supervision techniques. The adoption of technology makes the accessibility of education supervision activities easier.